Comprehensive Economic Benefits Evaluation Model of Greenhouse Photovoltaic (Journal of Solar Energy Research Updates, 2022)
Abstract: Photovoltaic integrated greenhouse has become an important form of deep coupling between new energy power generation and facility agriculture. Greenhouse photovoltaic power generation will affect the light environment, thermal environment, and water environment of facility agriculture. The precise coupling modeling method of greenhouse photovoltaics and loads is to carry out the basis for the calculation of comprehensive economic benefits of greenhouse photovoltaics. This paper studies the deep coupling modeling method of greenhouse photovoltaic and greenhouse load, and accurately calculates the changes in the light environment, thermal environment, and water environment regulation load of facility agriculture caused by the laying of greenhouse photovoltaics. Firstly, the greenhouse photovoltaic power generation model and the environmental regulation load model of facility agriculture are established; secondly, the coupling relationship between greenhouse photovoltaic power generation and facility agricultural load is described, and on this basis, the comprehensive economic benefits evaluation model of photovoltaic power generation is proposed. The 10kV medium-voltage distribution network and facility agricultural greenhouse that exist in the northern region are used as the research objects. It verifies the validity of the photovoltaic comprehensive economic benefits evaluation model proposed in this paper.